Sublocations of cancers of the oral cavity, oropharynx, hypopharynx, larynx, primary lymph node and other epidemiological features in a French Tropical Island in the Indian Ocean 2009-2013 - Delagranda, Antoine; Ferreira, Romain; Dufour, Xavier; Poisson, Maria; Leterme, Gaelle (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: This study had two objectives: firstly, to describe and compare sublocations of all cancer of the oral cavity, oropharynx, hypopharynx, larynx and primary carcinoma cervical lymph node diagnosed in Reunion Island, a tropical French overseas territory in the southern hemisphere between 2009 to 2013; and secondly others epidemiological features. Methods: A retrospective study included 621 patients diagnosed with cancer of the oral cavity, oropharynx, hypopharynx or larynx or primary cervical node between 2009 and 2013 in Reunion Island. 13 possible sublocations of cancer for mouth are described, 14 for larynx, 12 for oropharynx, 3 for hypopharynx, 8 for primary cervical lymph node. Demographic characteristics, data on alcohol consumption, smoking habits, HPV infection, denutrition were analyzed. Results: Cancer location consisted of oropharynx (36.2%), larynx (25.6%), oral cavity (20.8%), hypopharynx (13.8%), primary carcinoma lymph node (3.6%). Sublocations in oral cavity mainly concerned palatin tonsil and base tongue. Vocal fold was the mostly frequent sublocation involved in larynx. Cancer in oral cavity were portion out more homogeneously. Excluding primary lymph node, sex ratio was 7.7 and mean age was 60 years. Cancer consisted of squamous cell carcinoma in 99.1% of patients. 340/375 patients (81.25%) showed alcohol abuse; 309/359 (86.1%) were smokers; 31/184 (16.8%) had HPV infection. Conclusions: First study including all cases of pharyngolarynx and oral cavity cancer and depicting all sublocations involved in one series. We found no significant difference of distribution between sublocations for larynx but some for oropharynx and oral cavity compared to literature.